Effects of cytochrome P450 2B6 and constitutive androstane receptor genetic variation on Efavirenz plasma concentrations among HIV patients in Kenya. - Musa Otieno Ngayo; Margaret Oluka; Zachari Arochi Kwena; Wallace Dimbuson Bulimo; Faith Apolot Okalebo (PLoS ONE)
The effects of genetic variation of cytochrome P450 2B6 (CYP2B6) and constitutive androstane receptor (CAR) on efavirenz (EFV) plasma concentration was evaluated among 312 HIV patients in Nairobi Kenya. The EFV plasma concentration at steady-state were determined using ultra-high-performance liquid chromatography with a tandem quadruple mass spectrometer (LC-MS/MS). Thirteen CYP2B6 (329G>T, 341T>C, 444 G>T/C, 15582C>T, 516G>T, 548T>G, 637T>C, 785A>G, 18492C>T, 835G>C, 1459C>T and 21563C>T) and one CAR (540C>T) single nucleotide polymorphisms (SNPs) were genotyped using real-time polymerase chain reaction. HIV drug resistance mutations were detected using an in-house genotypic assay. The EFV concentration of patients ranged from 4 ng/mL to 332697 ng/mL (median 2739.5 ng/mL, IQR 1878-4891.5 ng/mL). Overall, 22% patients had EFV concentrations beyond therapeutic range of 1000-4000 ng/mL (4.5%% < 1000 ng/mL and 31.7% > 4000 ng/mL). Five SNPs (15582C>T, 516G>T, 785A>G, 983T>C and 21563C>T) were associated with higher EFV plasma concentration while 18492C>T with lower EFV plasma concentration (p<0.05). Strong linkage disequilibrium (LD) was observed for 15582C>T, 516G>T, 785A>G, 18492C>T, 983T>C, 21563C>T, 1459C>T and CAR 540C>T. Sixteen haplotypes were observed and CTGCTTCC, CTGCTTCT, TTGCTTCT and CGACCCCT were associated with high EFV plasma concentration. In multivariate analysis, factors significantly associated with EFV plasma concentration included; the presence of skin rash (β = 1379, 95% confidence interval (CI) = 3216.9-3416.3; p < 0.039), T allele of CYP2B6 516G>T (β = 1868.9, 95% CI 3216.9-3416.3; p < 0.018), the C allele of CYP2B6 983T>C (β = 2638.3, 95% CI = 1348-3929; p < 0.0001), T allele of CYP2B6 21563C>T (β = 1737, 95% CI = 972.2-2681.9; p < 0.0001) and the presence of 5 to 7 numbers of SNPs per patient (β = 570, 95% CI = 362-778; p < 0.0001) and HIV viral load ≤1000 cells/mL (β = -4199.3, 95% CI = -7914.9 --483.6; p = 0.027). About 36.2% of the patients had EFV plasma concentrations beyond therapeutic window, posing high risk of treatment failure or toxicity. The SNPs of CYP2B6 516G>T, CYP2B6 983T>C, 21563C>T, presence of higher numbers of SNPs per patient and haplotypes CTGCTTCC, CTGCTTCT, TTGCTTCT and CGACCCCT could efficiently serves as genetic markers for EFV plasma concentration and could guide personalization of EFV based ART treatment in Kenya.